Preparation of a magnetic multiwalled carbon nanotube@polydopamine/zeolitic imidazolate framework-8 composite for magnetic solid-phase extraction of triazole fungicides from environmental water samples. Issue 45 (16th July 2018) - Huang, Xiaodong; Liu, Yanan; Liu, Guangyang; Li, Lingyun; Xu, Xiaomin; Zheng, Shuning; Xu, Donghui; Gao, Haixiang
Abstract : A magnetic ZIF-8 composite was prepared based on Fe3 O4 /MWCNT@PDA and used as an adsorbent for MSPE of triazoles from environmental water samples. Abstract : A novel magnetic zinc-based zeolitic imidazolate framework (MMP/ZIF-8) has been prepared using a magnetic multiwalled carbon nanotube@polydopamine nanocomposite as the magnetic core and support. It was then used as an adsorbent for magnetic solid-phase extraction of triazole fungicides from environmental water samples. Successful synthesis of MMP/ZIF-8 was confirmed by material characterization, and the results showed that the synthetic composite has a high Brunauer–Emmett–Teller surface area (141.56 m 2 g −1 ), large total pore volume (0.636 mL g −1 ), and high superparamagnetism with a saturation magnetization of 44.1 emu g −1 . To evaluate the extraction performance of MMP/ZIF-8, the main parameters that affect the extraction efficiency were optimized. Under the optimal conditions, the developed method shows good linearity ( R 2 ≥ 0.9915) in the concentration range 1–400 μg L −1 . Low limits of detection (0.08–0.27 μg L −1, signal/noise = 3 : 1) and good precision (intraday relative standard deviation ≤ 7.73%, interday relative standard deviation ≤ 9.65%) are also achieved. The developed method was applied for analysis of triazole fungicides in environmental water samples.